Sebaran Timbal (Pb) di Perairan Wonorejo, Surabaya Jawa Timur - Tiento Rifqy Pribadi; Mahmiah; Rudi Siap Bintoro (Universitas Hang Tuah, 2023)
Wonorejo waters are one of the coasts that receive river flows (DAS) Jagir Wonokromo, Wonorejo, and Gunung Anyar rivers, Surabaya City. The Wonorejo coast is suspected of experiencing a decrease in water quality as there is a threshold value stipulated by the Decree of the Minister of Environment Number 51 of 2004 Research on the level of Pb pollution needs to be carried out because Wonorejo Waters are waters that are drained by industrial waste disposal around the estuary The method used in analyzing the content of heavy metal Pb is using Atomic Absorption Spectophotometry (AAS). From the research results, it was found that the highest Pb concentration value in this study was 0.31 mg/L while the lowest concentration value was 0.11 mg/L. The results of this study indicate that Wonorejo waters can be declared polluted because the concentration exceeds the NAV set by the Ministry of Environment and Forestry, which is 0.008 mg/L. The correlation between supporting parameters such as pH and salinity has a relationship with a fairly strong correlation value. The distribution of Pb is uneven due to the weak current velocity.